Uncoupling Protein 1 of Brown Adipocytes, the Only Uncoupler: A Historical Perspective - Ricquier, Daniel (Frontiers in Endocrinology, 2011)
Uncoupling protein 1 (UCP1), is a unique mitochondrial membranous protein devoted to adaptive thermogenesis, a specialized function performed by brown adipocytes. Whereas the family of mitochondrial metabolite carriers comprises ∼40 members, UCP1 is the only memberable to translocate protons through the inner membrane of brown adipocyte mitochondria. By this process, UCP1 uncouples respiration from ATP synthesis and therefore provokes energy dissipation in the form of heat while, also stimulating high levels of fatty acid oxidation. UCP1 homologs were identified but they are biochemically and physiologically different from UCP1. Thirty five years after its identification, UCP1 still appears as a fascinating component. The recent renewal of the interest in human brown adipose tissue makes UCP1 as a potential target for strategies of treatment of metabolic disorders.